Use of Nutritional Supplements Among Gym Clubs Participants in Sulaymaniyah City, Kurdistan Region of Iraq (International Journal of Occupational Safety and Health, 2021)
Introduction: Using dietary supplements has gained interest amongst people who desire to enhance their body composition. However, there are scant published data regarding the use of nutritional supplements and gym users. This study is to assess the intake of nutritional and dietary supplements among gym members in Sulaymaniyah city, Iraqi Kurdistan.Methods: The results of this study are based on the responses of one hundred gym members (aged over 18 years) to a self-manage questionnaire.Results: Almost half of the sample reported taking nutritional supplements and hormones. Thirty percent of the participants were consuming different protein powders. Most dietary supplement users noticed some side effects. Supplement users should always consult their physicians and been under the supervision of professional trainers and medical practitioners. In this manner, dietary supplements should not cause any side effects such as hypertension, hepatic disturbance, kidney disorders, hepatic, kidney disturbance, and muscle pain. However, some people (gym participants) may experience allergies, upset stomach/abdominal pain, and frequent urination.Conclusion: The usage rate of fitness supplements is very high, and the users are not aware of the potential consequences or dangers of unsupervised practice or unprescribed products. Therefore, there is an immediate need to promote consumers’ awareness of this issue, and the latest scientific data must be provided to users and coaches concerning consuming supplements.